INTER-RELATIONSHIP BETWEEN THE BRAIN-INTESTINE AXIS AND THE SEROTONERGIC MECHANISM IN OBESITY - Helena Vaz Tolloto, Gilce; Saragiotto, Laiz (Health and Society, 2022)
The enteric nervous system (ENS), communicates with the central nervous system (CNS) in a dynamic and complex fashion, through different pathways forming a bidimensional axis. This balance depends on several factors, between these systems and serotonin synthesis (5 HT). The gut synthesizes about 90% of the serotonin in our body and participates in various functions such as physiological control of the energy balance and maintenance of intestinal homeostasis. However, does serotonin that is synthesized in the gut have any impact on the brain and gut? Knowledge of the relationship between the gut-brain axis and participation of the serotonin system in the control of food intake and satiety in obesity is of great interest and importance, a fascinating and growing field. Objective: To describe and analyze interactions between the Central Nervous System (CNS) and the Enteric Nervous System (ENS), related to the serotonergic mechanism in obesity. Method: A bibliographic review included data from 134 scientific articles published between 2014 and 2021 in the PubMed, SciELO, LILACS, PsycINFO and ISI Web of Knowledge databases. Results and Conclusions: Interactions between the CNS and the ENS show gastrointestinal sensory motor functions. The gut produces around 90% of serotonin in our body. However, serotonin exerts approximately 80% of its action within the gut and most of the body’s 5-HT is secreted into the bloodstream, where it is largely and rapidly eliminated by the liver and lungs. CNS serotonergic neurons are independent from ENS serotonergic neurons and enteroendocrine cells. In addition, the blood-brain barrier is impermeable to serotonin. Therefore, serotonin synthesis in the brain is one of the major mechanisms that control hunger and satiety as well as carbohydrate ingestion, some of the contributing factors in the development of obesity. Integrative medicine represents a change in paradigm from a medical view of hermetically closed compartments to an interdisciplinary view between the brain-gut axis and the serotonin mechanism in obesity.